SDA and laterite applications in concrete: Prospects and effects of elevated temperature. Issue 1 (1st January 2017) - Awolusi, Temitope Funmilayo; Sojobi, Adebayo Olatunbosun; Afolayan, Joseph Olasehinde
Abstract: This research supports green eco-friendly construction through utilization of laterite and sawdust ash as fine aggregate and supplementary cementitious material in concrete. Critical literature review revealed that at fine aggregate replacement by laterite ≤50, 50–75 and 100%, mix ratios 1:2:4:0.56, 1:1.5:3:0.65 and 2:3:6:0.65 respectively are preferable for structural applications. Higher compressive strength losses of 32.81, 28.23 and 32.59% were recorded at elevated temperatures of 200, 400 and 600°C for SDA-modified laterized concrete while lower strength losses of 8.58, 7.91 and 3.74% were recorded for conventional laterized concrete. However, strength gain of 15.9% was recorded at 25°C ambient temperature for SDA-modified laterized concrete. Based on elevated temperature results, 10% SDA-modified laterized concrete at 45% optimum laterite content can only be used for production of load-bearing bricks and blocks and other non-structural applications. Further research efforts on green construction are required.